Citogenética em peixes de cabeceiras de dois riachos pertencentes à bacia do Alto rio Paraná, região de Toledo (PR) - Yano, Cássia Fernanda (2011)
Cytogenetics studies were carried out in two genera of fishes from Pindorama and Lopei streams, Upper Paraná River basin, with cytossistematic and ecologic-evolutionary approaches. In Heptapterus mustelinus, the first cytogenetics characterization in the genus was carried out, verifying 54 chromosomes (26m+18sm+4st+6a), which is a diploid number not observed among the Heptapteridae species till now studied. Differently from the others members of this family, multiple Ag-NORs and centromeric heterochromatin in almost all the chromosome of the complement were observed, being these heterochromatin CMA3+/DAPI- in nine chromosome pairs, beyond that coincident with Ag-NORs. These data show a different way in the karyotypic evolution of H. mustelinus in relation to the others Heptapteridae genus. In the genus Astyanax, an interpopulation comparative analysis was carried out in Astyanax aff. paranae, Astyanax fasciatus and Astyanax altiparanae from Pindorama and Lopei streams, in way to observe the chromosomal differentiation and the evolutionary trends in the three species. It was verified 48 and 50 chromosome in Astyanax aff. paranae and A. fasciatus, respectively, with interpopulation differences in the karyotypic formulae. The diploid number obtained to A. altiparanae was 50 chromosomes, with the same karyotypic formulae in both populations. The three species presented multiple Ag-NORs, with interpopulation differences observed in Astyanax aff. paranae and A. fasciatus. In relation to the heterochromatin distribution pattern, interpopulation differences were verified. The occurrence of Ag-NORs/CMA3+ was observed in the three species, besides DAPI+ bands in A. altiparanae. The results showed that Astyanax aff. paranae and A. fasciatus presented more conspicuous interpopulation differences than A. altiparanae populations, probably due bionomic characteristic that avoid the presence of Astyanax aff. paranae and A. fasciatus to upper segments in the streams, leading to the fixation of chromosomal rearrangements in these populations. However, the absence of interpopulation karyotypic differences in A. altiparanae suggests gene flow between the two populations. By the way, the present study showed that cytogenetics is an important tool in understanding the chromosomal mechanism involved in the evolutionary process in fishes group, and that the association to ecological studies is fundamental to the comprehension of dispersion process of some group of fishes.